Correlation Between Knowledge Level On Anxiety Level Post-Coronavac Vaccine at The Clinic of dr. Irma - Marintik Ilahi; Yusrin Aulia (Saintika Medika, 2021)
Vaccination is the government's effort to prevent the spread of the COVID-19 pandemic. Lack of knowledge about the Coronavac vaccine gives rise to various kinds of speculation, resulting in anxiety. This study attempts to analyze evaluate the correlation between knowledge level of public officers about the effects of Coronavac vaccine on anxiety level post-Coronavac vaccine at the dr. Irma Clinic.The study was an analytic observational study with a cross-sectional design, conducted on March 22, 2021. 62 public officers who received the Coronavac vaccine at the dr. Irma Clinic was enrolled. The sampling technique used was total sampling. The data analysis used was the Mann-Whitney test.The result showed that 39 (62.9%) respondents had a good level of knowledge. 42 (67.7%) respondents showed no sign of anxiety. There was a tendency that the better the level of knowledge, the less anxious, and vice versa, the less knowledge, the more respondents experience both mild and moderate anxiety. From the Mann Whitney test results, the p-value was 0.000 (sig < 0.05).There was significant correlation between knowledge level of public officers about the effects of Coronavac vaccine on anxiety level post-Coronavac vaccine at the dr. Irma Clinic.